Measuring mentalizing: A comparison of scoring methods for the hinting task. Issue 2 (9th May 2020) - Klein, Hans S.; Springfield, Cassi R.; Bass, Emily; Ludwig, Kelsey; Penn, David L.; Harvey, Philip D.; Pinkham, Amy E.
Abstract: Objective: The Social Cognition Psychometric Evaluation (SCOPE) study supported the utility and practicality of the Hinting task as a measure of social cognition/mentalizing in clinical trials, specifically with the SCOPE authors' stringent scoring system. However, it remains unclear whether the SCOPE scoring system is necessary for the task to be judged as psychometrically sound. Method: Independent raters rescored data from the three phases of SCOPE using the Hinting task's original scoring criteria. Psychometric properties of the task when scored with the original criteria versus more stringent SCOPE criteria were compared in a large sample of individuals with chronic schizophrenia ( n = 397) and matched controls ( n = 300) as well as a smaller sample of individuals with early psychosis ( n = 38) and controls ( n = 39). Results: In both samples, SCOPE criteria resulted in lowered average scores and reduced ceiling effects. Further, revised scoring resulted in strengthened relationships between the hinting task and outcome measures in the chronic sample, and better differentiated early psychosis patients from controls. Conversely, test‐retest reliability and internal consistency estimates were not improved using revised scoring and remained suboptimal, particularly for healthy controls. Conclusion: Overall, SCOPE scoring criteria improved some psychometric properties and clinical utility, suggesting that these criteria should be considered for implementation.